Enantiotopic Discrimination by Coordination‐Desymmetrized meso‐Ligands. Issue 6 (22nd January 2020) - Li, Yutang; Lidskog, Anna; Armengol‐Relats, Helena; Pham, Thanh Huong; Favraud, Antoine; Nicolas, Maxime; Dawaigher, Sami; Xiao, Zeyun; Ma, Dayou; Lindbäck, Emil; Strand, Daniel; Wärnmark, Kenneth
Abstract: The first examples of enantiopure catalysts that are chiral merely due to coordination of different metal ions at enantiotopic positions of an achiral meso ‐ligand are reported. These catalysts exhibit a pseudo‐ C s symmetry and are able to catalyze reactions demanding simultaneous involvement of two catalytic sites. The latter was demonstrated by application in the asymmetric ring‐opening of meso ‐epoxides. Abstract : Just barely chiral : A meso‐ligand, desymmetrized by coordination of two different metal ions, gives a pseudo‐meso catalyst. This catalyst system mediates opening of meso‐epoxides in moderate ee's and excellent yields.